Does Memorable Tourism Experience (MTE) Influence Revisit Intention of Domestic Tourists? (A Case Study at Tanah Lot Tourist Attraction, Tabanan Regency) - Wiryaguna, I Gede Patria; Susianti, Hartanti Woro; Widana, Ida Bagus Gede Agung (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
A Memorable Tourism Experience (MTE) is a notable experience that travelers recall and build on when describing a visit to a particular tourism location. This experience can be used to assess the level of interest and its influence on the likelihood of returning to the destination. The purpose of this study is to look into the impact of MTE on the likelihood of domestic tourists returning to Tanah Lot Tourist Attraction in Tabanan Regency. The research employs a quantitative approach, using both primary and secondary data sources. Data from 350 respondents were collected via a questionnaire and subsequently analyzed using multiple linear regression techniques with SPSS version 25 for Windows. The findings indicate that the dimensions of hedonism, local culture, refreshment, involvement, meaningfulness, and knowledge have a positive and significant effect on the revisit intention of domestic tourists to Tanah Lot Tourist Attraction. Conversely, the dimension of novelty has a positive but not significant effect. The simultaneous test shows that MTE has a positive and significant effect on the revisit intention of domestic tourists to Tanah Lot Tourist Attraction. The determination test results reveal an R² value of 0.636, indicating that Memorable Tourism Experience accounts for 63.6% of the variance in revisit intention among tourists at Tanah Lot Tourist Attraction. The remaining 36.4% is influenced by other variables not examined in this study.